2020
DOI: 10.1111/jcpt.13232
|View full text |Cite
|
Sign up to set email alerts
|

Association between inosine triphosphatase rs1127354 polymorphisms and ribavirin‐induced anaemia and outcome in hepatitis C virus‐infected patients: A meta‐analysis

Abstract: What is known and objectives The association between inosine triphosphatase (ITPA) rs1127354 polymorphisms in HCV‐infected patients receiving ribavirin (RBV)‐based therapy, and the risk of adverse drug reaction and outcomes is still unclear. A meta‐analysis was conducted to summarize and clarify this association systematically. Methods A comprehensive search was performed in PubMed, Embase and Web of Sciences, and twenty‐two studies were selected from the literature search. Pooled odds ratio (OR) and 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In addition, these polymorphisms were linked to a sustained virological response in HCV patients (Rembeck et al, 2014). Metanalyses further support these associations (Ma et al, 2020; Pineda‐Tenor et al, 2015).…”
Section: Itpase Deficiency and Clinically Relevant Variants In Itpamentioning
confidence: 81%
“…In addition, these polymorphisms were linked to a sustained virological response in HCV patients (Rembeck et al, 2014). Metanalyses further support these associations (Ma et al, 2020; Pineda‐Tenor et al, 2015).…”
Section: Itpase Deficiency and Clinically Relevant Variants In Itpamentioning
confidence: 81%
“…Literature learned from a few studies discussed the effect of rs7170101 polymorphism. They also found statistical evidence of an association between ribavirin dose reduction and ITPA polymorphism [ 4 ]. A real-life study was conducted on HCV genotype 2 patients, and it was observed that regardless of previous antiviral treatment history sofosbuvir-based treatment schedules were associated with good tolerability and SVR achievement rates, without a significant impact, on treatment ribavirin dose reductions [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ribavirin-induced hemolytic anemia is the cause of ribavirin dose reduction and therapy discontinuation in 10–20% of patients which is also reported to impact antiviral therapy outcomes. The continuous advancement in the discovery of antiviral agents targeting various stages of HCV life cycle is leading towards effective interferon free direct acting antiviral (DAA) therapy [ 4 6 ]. The arrival of DAA along with ribavirin against HCV infection resulted over 90–95% SVR rates along with lesser side effects [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation